Molecular characterization of antimicrobial resistance in Klebsiella pneumoniae isolated from Brazilian dairy herds - Nobrega, Diego Borin; Calarga, Aline Parolin; Nascimento, Leandro Costa; Chande Vasconcelos, Carla Gasparotto; de Lima, Eliane Martins; Langoni, Helio [UNESP]; Brocchi, Marcelo (American Dairy Science Association, 2021)
In this observational study, phenotypic and genotypic patterns of antimicrobial resistance (AMR) in Klebsiella pneumoniae isolated from intramammary infections, clinical mastitis, fresh feces, rectal swabs, animal hindlimbs, and bulk tank milk samples from Brazilian dairy herds were investigated. In addition, we identified specific genetic variants present among extended-spectrum β-lactamase (ESBL) producers. We obtained 169 isolates of K. pneumoniae from 2009 to 2011 on 24 Brazilian dairy farms located in 4 Brazilian states. The AMR profile of all isolates was determined using disk-diffusion assays. The antimicrobial panel included drugs commonly used as mastitis treatment in Brazilian dairy herds (gentamicin, cephalosporins, sulfamethoxazole-trimethoprim, tetracycline) as well as antimicrobials of critical importance for human health (meropenem, ceftazidime, fluoroquinolones). The K. pneumoniae isolates resistant to tetracycline, fluoroquinolones, sulfamethoxazole-trimethoprim, or chloramphenicol were screened for presence of drug-specific AMR genes [tet, qnr, aac(6')-Ib, floR, catA2, cm1A, dfr, sul] using PCR. In addition, we identified ESBL genes present among ESBL-producers by using whole genome sequencing. Genomes were assembled and annotated, and patterns of AMR genes were investigated. Resistance was commonly detected against tetracycline (22.5% of all isolates), streptomycin (20.7%), and sulfamethoxazole-trimethoprim (9.5%). Antimicrobial resistance rates were higher in K. pneumoniae isolated from intramammary infections in comparison with isolates from feces (19.2 and 0% of multidrug resistance in intramammary and fecal isolates, respectively). In contrast, no difference in AMR rates was observed when contrasting hind limbs and isolates from intramammary infections. The genes tetA, sul2, and floR were the most frequently observed AMR genes in K. pneumoniae resistant to tetracycline, sulfamethoxazole-trimethoprim, and chloramphenicol, respectively. The tetA gene was present exclusively in isolates from milk. The genes blaCTX-M8 and blaSHV-108 were present in 3 ESBL-producing K. pneumoniae, including an isolate from bulk tank milk. The 3 isolates were of sequence type 281 and had similar mobile genetic elements and virulence genes. Our study reinforced the epidemiological importance and dissemination of blaCTX-M-8 pST114 plasmid in food-producing animals in Brazil.
Keywords: antimicrobial resistance; extended-spectrum β-lactamase; Klebsiella pneumoniae; mastitis